PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS CANVA PADA MATA PELAJARAN IPA KELAS III SD NEGERI 1 RAPPANG - Andi Diana Parha Mursidah; Nurmayanti; Syamsunir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to produce canva-based learning video media and test the validity and practicality of canva-based learning videos in grade III elementary schools. With the ADDIE model development method which includes analysis, design, development, implementation and evaluation is used as the development procedure of this research. Based on the results of the study, it is known that the validation level of media experts is 90%, also using high criteria; and 92% validation by material experts, indicating a very valid level of validity. In addition, in the practicality assessment questionnaire score which was considered very well applied by both teachers and students, with an assessment of 92% from teachers and 85.6% from students so that the criteria were obtained with a very practical level of practicality. The findings of this study indicate that learning videos using the Canva application in grade III elementary school science subjects on the material of changes in the form of objects are declared valid and practical.